Role of Strain Rate in the Pathogenesis of Ventilator-Induced Lung Edema*. Issue 9 (September 2016) - Protti, Alessandro; Maraffi, Tommaso; Milesi, Marta; Votta, Emiliano; Santini, Alessandro; Pugni, Paola; Andreis, Davide T.; Nicosia, Francesco; Zannin, Emanuela; Gatti, Stefano; Vaira, Valentina; Ferrero, Stefano; et al.
Abstract : Objective: Lungs behave as viscoelastic polymers. Harms of mechanical ventilation could then depend on not only amplitude (strain) but also velocity (strain rate) of lung deformation. Herein, we tested this hypothesis. Design: Laboratory investigation. Setting: Animal unit. Subjects: Thirty healthy piglets. Interventions: Two groups of animals were ventilated for 54 hours with matched lung strains (ratio between tidal volume and functional residual capacity) but different lung strain rates (ratio between strain and inspiratory time). Individual strains ranged between 0.6 and 3.5 in both groups. Piglets ventilated with low strain rates had an inspiratory-to-expiratory time ratio of 1:2–1:3. Those ventilated with high strain rates had much lower inspiratory-to-expiratory time ratios (down to 1:9). Respiratory rate was always 15 breaths/min. Lung viscoelastic behavior, with ventilator setting required per protocol, was "quantified" as dynamic respiratory system hysteresis (pressure-volume loop [in Joules]) and stress relaxation (airway pressure drop during an end-inspiratory pause [in cm H2 O]). Primary outcome was the occurrence of pulmonary edema within 54 hours. Measurements and Main Results: On average, the two study groups were ventilated with well-matched strains (2.1 ± 0.9 vs 2.1 ± 0.9; p = 0.864) but different strain rates (1.8 ± 0.8 vs 4.6 ± 1.5 s –1 ; p < 0.001), dynamic respiratory system hysteresis (0.6 ± 0.3 vs 1.4 ± 0.8 J; p = 0.001), and stress relaxation (3.1 ± 0.9 vs 5.0 ± 2.3 cm H2 O; p = 0.008). The prevalence of pulmonary edema was 20% among piglets ventilated with low strain rates and 73% among those ventilated with high strain rates ( p = 0.010). Conclusions: High strain rate is a risk factor for ventilator-induced pulmonary edema, possibly because it amplifies lung viscoelastic behavior. Abstract : Supplemental Digital Content is available in the text.